Medidas de entropia alternativas para caracterização da existência de clãs em famílias de domínios de proteínas - Albuquerque Neto, Simão Coutinho de (2018)
The sequencing and cataloging of proteins is an initiative that seeks a complete and accurate classification of protein domains. It is really important in the determination of the cause of genetic diseases and in the discovery of effective treatments for them. The domains which have similar sequences, structures and functions are grouped into families. Based on the opinion of expert biologists regarding the similarity of functions, some families are collected in clans. On the present work the ANOVA statistics is used to verify the legitimacy of the classification of protein families in clans. The results with the (100 × 200) and (100 × 100) representative family blocks are presented and discussed.